Psychometric evaluation of the "Ser Bachiller 2020-Régimen Costa" applying the Differential Functioning of the Items - Ajila Sanmartin, Jhon Paul (2022)
This study shows the results of the Differential Item Functioning (DIF) detection analysis of the items of the Ser Bachiller assessment of the Costa cycle, which was applied in 2020 to high school graduates and applicants to public universities in Ecuador. The Mantel-Haenszel method, a well-known method used by the Educational Testing Service, was used. The presence of DIF was explored based on four axes of analysis: sex of the subject, area of settlement, ethnic self-identification group and type of schooling. It is concluded that the items of the Ser bachiller Costa 2020 are not affected by differential functioning. This supports the hypothesis that the test items applied by Ineval do not favor or disadvantage certain specific population groups, so the different population groups evaluated are not affected in any way by the design of the Ser Bachiller assessment.